PENINGKATAN PEMAHAMAN GOOD MANUFACTURING PRACTICE BAGI SISWA SMK NEGERI H. MOENADI UNGARAN KABUPATEN SEMARANG - Kunarto, Bambang; Iswoyo, Iswoyo; Putri, Aldila Sagitaning; Putri, Soraya Kusuma (Universitas Semarang, 2021)
ABSTRACT Knowledge of good manufacturing practice is very important to be known by food industry players to provide protection to the community with the aim of improving food safety, quality and preventing economic losses. Counseling on good manufacturing practice is very appropriate to add insight to students of SMK Negeri H. Moenadi Ungaran Semarang Regency, because one of the competency standards for SMK graduates is that students have the ability to carry out their expertise by applying the principles of safety, health and environmental security. SMK Negeri H. Moenadi Ungaran Semarang Regency is a Vocational High School that has expertise in agribusiness processing of agricultural products (APHP), where the food industry is in line with the fields of work of its graduates. This activity aims to provide information in the form of counseling to improve understanding of good manufacturing practices for students of SMK Negeri H. Moenadi Ungaran, Semarang Regency. The activities carried out include an explanation of food safety, good manufacturing practices, chemical contamination in food and the application of good manufacturing practices in meat processing. Based on the activities that have been carried out, it can be concluded that this extension activity can improve students' understanding of and good manufacturing practices Keywords: food safety, good manufacturing practice, SMK Negeri H. Moenadi